DATA COLLECTION IN THE OSINT INVESTIGATION TECHNOLOGY CHAIN - Korobeinikova, Tetiana; Symak, Ihor (Sworld-Us Conference proceedings, 2024)
The work is devoted to the study of the data collection process within the OSINT investigation. Approaches to the formalization of this process are proposed, in particular, the "intelligence cycle" model. The focus is on Gibson's model of the intelligence